2015
DOI: 10.3389/fnhum.2015.00013
|View full text |Cite
|
Sign up to set email alerts
|

Personality and intentional binding: an exploratory study using the narcissistic personality inventory

Abstract: When an individual estimates the temporal interval between a voluntary action and a consequent effect, their estimates are shorter than the real duration. This perceived shortening has been termed “intentional binding”, and is often due to a shift in the perception of a voluntary action forward towards the effect and a shift in the perception of the effect back towards the action. Despite much work on binding, there is virtually no consideration of individual/personality differences and how they affect it. Nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…To this end, we show that the signal quality is acceptable for the purpose of this study. This corresponds with prior studies demonstrating that this headset produces acceptable data quality and that it reproduces brain responses (both event-related potentials and frequency based responses) comparable to what has been found in studies with higher-resolution systems (Badcock et al, 2013 ; Grummett et al, 2014 ; Christopher et al, 2015 ; Wang et al, 2015 ), including emotional processing (Harmon-Jones et al, 2010 ; Khushaba et al, 2013 ), and even in mobile settings (Allison et al, 2010 ; Debener et al, 2012 ). This said, further support from these findings is needed from studies using high-resolution EEG and other neuroimaging approaches.…”
Section: Discussionsupporting
confidence: 85%
“…To this end, we show that the signal quality is acceptable for the purpose of this study. This corresponds with prior studies demonstrating that this headset produces acceptable data quality and that it reproduces brain responses (both event-related potentials and frequency based responses) comparable to what has been found in studies with higher-resolution systems (Badcock et al, 2013 ; Grummett et al, 2014 ; Christopher et al, 2015 ; Wang et al, 2015 ), including emotional processing (Harmon-Jones et al, 2010 ; Khushaba et al, 2013 ), and even in mobile settings (Allison et al, 2010 ; Debener et al, 2012 ). This said, further support from these findings is needed from studies using high-resolution EEG and other neuroimaging approaches.…”
Section: Discussionsupporting
confidence: 85%
“…It has also been shown that psychosis-related and positive social personality traits may predict decreases or increases in the prospective intentional binding depending on individual environmental control (Di Plinio et al, 2019a). Furthermore, intentional binding differs between high-and low-hypnotizable individuals (Lush et al, 2019) and correlates with narcissistic personality traits (Hascalovitz and Sukhvinder, 2015). These studies consistently demonstrate interindividual differences in the tendency to experience an enhanced or reduced sense of agency.…”
Section: Introductionmentioning
confidence: 78%
“…How then can these results be reconciled with the larger literature? Even with the limitations that Hascalovitz and Obhi ( 2015 ) acknowledge prevent the generalizability of their study, their findings suggest that with narcissism comes a heightened sense of effectiveness and control over willful action. One possibility suggested by clinical reports (Ronningstam, 2009 ; Links, 2015 ) is that persons with NPD alternate from hyper-agency to passivity and flatness.…”
mentioning
confidence: 86%
“…Hascalovitz and Obhi ( 2015 ) examined whether narcissism was related to a disturbed sense of agency. Using the construct of intentional binding, which is thought to be a core element of agency, they sought to determine whether the speed with which a voluntary action was perceived to have a consequent effect differed according to levels of narcissism.…”
mentioning
confidence: 99%